2021
DOI: 10.3389/fpls.2021.748287
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphorylation Changes During Systemic Acquired Resistance in Arabidopsis thaliana

Abstract: Systemic acquired resistance (SAR) in plants is a defense response that provides resistance against a wide range of pathogens at the whole-plant level following primary infection. Although the molecular mechanisms of SAR have been extensively studied in recent years, the role of phosphorylation that occurs in systemic leaves of SAR-induced plants is poorly understood. We used a data-independent acquisition (DIA) phosphoproteomics platform based on high-resolution mass spectrometry in an Arabidopsis thaliana mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 100 publications
(117 reference statements)
0
8
0
Order By: Relevance
“…The plant PTI is activated by the recognition of PAMPs and PRRs, which are mainly RLKs (Wu et al, 2019). In our recent study, we found the phosphorylation levels of 17 RLKs were significantly changed in systemic leaves of SAR-induced plants (Zhou et al, 2021), suggesting that these proteins are also involved in SAR establishment in cells of systemic leaves. Therefore, we can speculate that plant EVs also contain PAMPs released by the pathogens, which contribute to the induction of local resistance and SAR (Figure 2).…”
Section: Role S Of Pl Ant E Vs In P Ti E Ti and Sarmentioning
confidence: 90%
“…The plant PTI is activated by the recognition of PAMPs and PRRs, which are mainly RLKs (Wu et al, 2019). In our recent study, we found the phosphorylation levels of 17 RLKs were significantly changed in systemic leaves of SAR-induced plants (Zhou et al, 2021), suggesting that these proteins are also involved in SAR establishment in cells of systemic leaves. Therefore, we can speculate that plant EVs also contain PAMPs released by the pathogens, which contribute to the induction of local resistance and SAR (Figure 2).…”
Section: Role S Of Pl Ant E Vs In P Ti E Ti and Sarmentioning
confidence: 90%
“…In this study, a marked increase in the number of differentially phosphorylated proteins in systemic leaves inoculated with the pathogenic bacteria Pseudomonas syringae pv. Maculicola was observed [30]. The observed differentially phosphorylated proteins included several transcription factors, kinases, and a variety of defense response-related proteins.…”
Section: Phosphorylation: Regulation Of Plant Signalling Processesmentioning
confidence: 96%
“…ACQUIRED RE S IS TAN CE SAR is an inducible defensive response of plants triggered by localized pathogen attack. It can induce immunity to subsequent pathogen infection in the whole plant within a few days (Schnake et al, 2020;Zhou et al, 2021). Some long-distance signals synthesized at the infection site during SAR can be translocated to systemic tissues via phloem or volatilization to induce disease resistance (Chanda et al, 2011;Chaturvedi et al, 2012;Jung et al, 2009;Riedlmeier et al, 2017).…”
Section: Ltps Contribute To Pl Ant Re S Is Tan Ce Re S P On S E S By ...mentioning
confidence: 99%